Analysis of low-frequency vibration in a steam turbine based on closed-loop system identification - Yabui, Shota; Kotsuchihashi, Hiroki; Inoue, Tsuyoshi (Journal of Low Frequency Noise, Vibration and Active Control, 2023)
Steam turbines are used to generate thermal power in electric power plants. They are important industrial equipment that support societal infrastructure. The stable operation of steam turbines is necessary to maintain long-term electrical power supply. However, low-frequency vibration, which is referred to as steam-whirl-induced vibration, is a self-excited vibration that can damage turbines and hinders stable operation. Therefore, a prediction model and stable margin for steam-whirl-induced vibration in steam turbines should be developed. In this study, we propose a method for modeling steam-whirl-induced vibration using closed-loop system identification. This method directly creates a vibration model from the rotor displacement data. The gain, damping, and natural frequency of the vibration were calculated using this model. Moreover, an equation for the relationship between the damping and load was derived using the model, and the stable margin for increasing the load was estimated. Steam-whirl-induced vibration was modeled using the proposed method for the displacement data obtained from an actual steam turbine. The characteristics of the model are in good agreement with the experimental results, indicating the feasibility of using the model to predict steam-whirl-induced vibration.